(untitled) (INNOVATIVE ECONOMY, 2019)
Malyi I.Y., Koroliuk T.O. INFORMATIZATION OF SOCIETY AND PUBLIC ECONOMIC SECURITY ADMINISTRATION Purpose. The aim of the article is description of the interdependencies of the development of informatization of society and the improvement of public administration in overcoming the economic threats to the existence of the state of Ukraine. Methodology of research. Achieving this goal is based on the use of the research methodology of the innovative and informational type of economic development and public (state) management. The following specific methods are used: systematic – to disclose the directions of the influence of information transformation on all spheres of the functioning of society; ecumenical (interdisciplinary) – to disclose institutional changes in public administration due to new threats to territorial integrity and economic security; analysis – to characterize the trends in the application of information technology in economics and management; statistical methods – to assess the magnitude of economic threats to the functioning of society and the substantiation of anti-crisis measures by the state. Findings. It is established that the study of the interaction between informatization of society and new public administration for the purpose of localization of economic threats to statehood necessarily implies the use of systematic analysis, ecumenical (interdisciplinary) approach, theories of institutional changes and systemic crisis of civilization. The principles of the mechanism of interaction “informatization of society – new public administration – guarantees of national economic security” are substantiated, based on the following logic: the fundamental instinct of self-preservation of the person leads them to unification in the state as the highest and long-lasting social, legal, political and economic forms of joint activity of people; and the state, first and foremost protecting the interests of the people who shape the public interest as a whole, is obliged to protect them as national in the international arena, including national economic security. It is proved that the rapid development of information transformation and new innovative products in the economy undermines the hierarchy of relationships, contributes to the active expansion of network structures that radically change human values, the format of interaction of citizens (consumers) with business and the state, puts new requirements for the game from the state. It is revealed that the new public administration is characterized by productivity, marketing approach to studying the needs of citizens and threats to their lives; decentralization; reporting on the results that is possible under the conditions of introduction of electronic governance and changes in the legislative field. It is substantiated that strategic goals of implementation of electronic government are overcoming information inequality, restructuring of relations with citizens, improvement of technology of public management and administration in order to ensure transparency, accessibility and convenience of receiving public services by citizens, which opens the possibility of their real participation in making public management decisions in order to localize corruption, shadowing, raiding as factors of economic threats to statehood. Originality. The scientific novelty of the study is to substantiate the author’s approach to the dialectics of the interaction of “informatization of society – the new public administration – national economic security” in the context of continuous information transformation, institutional changes and global challenges. Practical value. The theoretical approaches developed by the authors to the analysis of the influence of informatization of society, new public administration and national economic security can become the fundamental basis for the development of anti-crisis policies in Ukraine with the aim of ensuring territorial integrity, the safety of citizens and their well-being. Key words: informatization of society; new public administration; economic security; state sovereignty; openness; transparency; electronic governance.